105 DEG C temperature-resistant B1-grade high-flame-retardant cable material as well as application and preparation method thereof

By optimizing the material formula and process conditions, a high flame retardant silane cross-linked halogen-free, low smoke flame retardant polyolefin cable material with temperature resistance of 105℃ has been developed, which solves the stability and performance balance of automotive wire materials when the line is released at high speed at thin-wall or ultra-thin-wall insulating layers, and achieves the improvement of efficient production and environmental protection performance.

CN119823472AInactive Publication Date: 2025-04-15HANGZHOU YITIAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510315824.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When preparing thin-wall or ultra-thin-wall insulating layers of existing automotive wire materials, it is difficult to take into account high-speed wire release and stability, and it is prone to glue breakage, resulting in a decrease in production capacity.

Method used

By optimizing the material formulation and process conditions, a temperature-resistant B1 grade high flame retardant silane cross-linked halogen-free low smoke flame retardant polyolefin cable material, including material A and material B, uses specific resins, flame retardants, compatibility agents and catalysts, combined with the process flow of twin screw extruders and high-speed mixers to ensure the stability and performance balance of the material when it is released at high speed.

Benefits of technology

The stability and performance balance of the preparation of thin-wall or ultra-thin-wall automotive wire insulation layers at a higher linear release speed is achieved, which avoids the occurrence of glue breakage, improves production capacity, and meets the high flame retardancy and environmental protection requirements of automotive wires.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a 105 DEG C temperature-resistant B1-grade high-flame-retardant cable material as well as application and a preparation method thereof, and relates to the field of manufacturing of high polymer materials and cables. The material A comprises low-melt-index high-density polyethylene, high-melt-index low-density polyethylene, a modified elastomer, micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite, a halogen-free phosphorus-nitrogen flame retardant, vinyl trimethoxy silane, dicumyl peroxide, a maleic anhydride grafted ethylene-butyl acrylate copolymer, an antioxidant and a lubricant; the material B comprises high-melt-index high-density polyethylene, dibutyltin dilaurate, red phosphorus microencapsulated particles, an antioxidant and a lubricant, and the cable material can be prepared by mixing and crosslinking the material A and the material B. The cable material overcomes the defect that in the prior art, glue breaking is prone to occurring during high-speed paying-off, the production capacity is effectively improved, and the production cost is reduced; and the contradiction that the thin wall and the high flame retardance are difficult to consider in the prior art is broken through.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials and cable manufacturing, and in particular to a 105°C temperature-resistant B1-grade highly flame-retardant cable material and its application and preparation method. Background Art

[0002] In recent years, with the rapid economic development and the increasing GDP, people's living standards have been continuously improved, and cars have gradually become a household necessity. Therefore, the sales volume of cars has been rising year by year, and at the same time, higher and higher requirements have been put forward for the new performance of cars. For example, the car wires are required to be lightweight and thinner (some require the conductor area to be less than 0.5 square millimeters), etc., which puts higher and higher requirements on the insulation layer of the wires on the car. It requires not only thin walls (for example, the thickness of the insulation layer is required to be 0.25-0.50mm), but also high and low temperature resistance, scratch resistance, and good flame retardancy. At the same time, based on the influence of production capacity, the pay-off speed is required to be high. However, the original automotive wire materials on the market are basically unable to be able to pay-off at high speed when preparing thin-walled or even ultra-thin-walled automotive wire insulation layers, resulting in a serious decline in production capacity, and it is easy to break the glue when paying off quickly.

[0003] For example, Chinese invention patent CN112409671A discloses a silane self-crosslinking halogen-free low-smoke flame-retardant polyolefin automotive raw material and its preparation method and application, which includes material A and material B, the raw materials of material A include a first base resin, a compatibilizer, a first flame retardant, silane, an initiator, and a first antioxidant, the raw materials of material B include a second base resin, a second flame retardant, a second antioxidant, and a catalyst, the first base resin and the second base resin are independently composed of low melt index high-density polyethylene and high melt index high-density polyethylene, the melt index of the low melt index high-density polyethylene is 0.5-2.0g / 10min, and the melt index of the high melt index high-density polyethylene is 8.0-30.0g / 10min; wherein, in terms of mass percentage, the first base resin or the second base resin In the resin, low melt index high density polyethylene accounts for 30%-70%, and high melt index high density polyethylene accounts for 30%-70%; the compatibilizer is composed of maleic anhydride grafted ethylene butyl acrylate copolymer and maleic anhydride grafted polyethylene, and the feeding mass ratio of the maleic anhydride grafted ethylene butyl acrylate copolymer to the maleic anhydride grafted polyethylene is 1:1.8-2.2; the absolute value of the difference between the specific gravity of the A material and the specific gravity of the B material is less than 0.05; although the polyolefin automotive raw wire material can be quickly cross-linked under natural conditions and still has excellent physical and mechanical properties under the premise of having a high pay-off speed, in fact, its prerequisite is to produce an insulating layer with a conventional wall thickness. For thin-walled or even ultra-thin-wall automotive wire insulation layers, it cannot achieve a high pay-off speed, otherwise it is easy to cause glue breaking during fast pay-off. Summary of the invention

[0004] The present application provides an improved 105°C temperature-resistant B1 grade highly flame-retardant silane cross-linked halogen-free low-smoke flame-retardant polyolefin cable material by comprehensively optimizing material formulation and process conditions, which solves the stability and performance balance problems of thin-walled insulation layers during high-speed pay-off, and at the same time achieves the preparation of thin-walled or even ultra-thin-walled automotive wire insulation layers at a higher pay-off speed without glue breaking.

[0005] A 105°C temperature-resistant B1-grade highly flame-retardant cable material and its application and preparation method, wherein the cable material comprises, by mass percentage: 60%-70% of A material and 30%-40% of B material; In terms of mass percentage, the raw materials of the material A include: 60%-85% of the first base resin, 38%-52% of the first flame retardant, 1%-2% of the silane coupling agent, 0.3%-0.5% of the initiator, 2%-4% of the first compatibilizer, 0.3%-0.7% of the antioxidant, and 0.1%-0.3% of the lubricant; In terms of mass percentage, the raw materials of the B material include: 40%-50% of the second base resin, 0.05%-0.1% of the catalyst, 1%-2% of the second flame retardant, 0.3%-0.7% of the antioxidant, and 0.1%-0.3% of the lubricant; The first base resin is composed of low melt index high density polyethylene, high melt index low density polyethylene and modified elastomer, wherein the modified elastomer can enhance the low temperature impact performance of the material, the second base resin is high melt index high density polyethylene, the feed mass ratio of the low melt index high density polyethylene, the high melt index low density polyethylene and the modified elastomer is 3-4:2-3:1-1.5, the melt index of the low melt index high density polyethylene is 0.8-1.5g / 10min, the melt index of the high melt index low density polyethylene is 8-12g / 10min, and the melt index of the high melt index high density polyethylene is 20-30g / 10min; The first flame retardant is composed of micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite and halogen-free phosphorus and nitrogen flame retardant, wherein the expanded graphite can enhance the expansion insulation performance while reducing smoke density and toxicity, the second flame retardant is red phosphorus microencapsulated particles, which can enhance flame retardancy while reducing smoke density, the first flame retardant, micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite and halogen-free phosphorus and nitrogen flame retardant feed mass ratio of 2-2.5: 1-1.5: 0.3-0.5: 0.5-0.7; The silane coupling agent is vinyl trimethoxysilane, the initiator is diisopropylbenzene peroxide, which can increase the crosslinking rate, the first compatibilizer is maleic anhydride grafted ethylene butyl acrylate copolymer, which can improve the dispersibility of the filler and the substrate interface, the antioxidant is hindered phenol antioxidant 1010+phosphite antioxidant 168, and the mass ratio of the hindered phenol antioxidant 1010 to the phosphite antioxidant 168 in the antioxidant is 2-4:1-3, the lubricant is zinc stearate, which can optimize the shearing and wire-laying performance during processing, and the catalyst is dibutyl tin dilaurate.

[0006] A method for preparing a 105°C temperature-resistant B1-grade highly flame-retardant cable material, comprising the following steps: S1. Add the first base resin and the first flame retardant into a high-speed mixer, set the speed to 1000 rpm, and mix for 3-5 minutes; S2, add the first compatibilizer and antioxidant, continue mixing for 2 minutes, add the silane coupling agent dropwise during the mixing process, and keep the mixer running at 300-500 rpm for 3-5 minutes to ensure that the silane is evenly coated on the filler surface; S3, putting the dry mixed materials into a twin-screw extruder for melt mixing; S4, adding initiator during extrusion to ensure full dispersion, the extruded material is cooled through a water tank, and cut into granules by a pelletizer to obtain material A; S5, adding the second base resin and the second flame retardant into a high-speed mixer, setting the speed to 1000 rpm, and mixing for 3-5 minutes; S6. Add antioxidant and lubricant, continue mixing for 2 minutes, gradually add catalyst premix to the dry mixed material, keep the mixer running at 300-500 rpm for 2-3 minutes to ensure that the catalyst is evenly dispersed; S7, putting the dry-mixed materials into a twin-screw extruder for mixing, cooling the extruded materials through a water tank, and cutting them into granules with a pelletizer to obtain material B; S8, after material A and material B are evenly mixed, the cable is extruded, the temperature of the extruder is controlled at 160-200°C, and the pay-off speed is adjusted to 800m / min; S9. Place the processed cable product at 25°C for 48-72 hours to complete the cross-linking reaction.

[0007] Preferably, the extruder temperature in S8 is 180°C.

[0008] Preferably, in the first flame retardant, the mass ratio of micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite and halogen-free phosphorus and nitrogen flame retardant is 2:1:0.4:0.6.

[0009] Preferably, in the first base resin, the feed mass ratio of the low melt index high density polyethylene, the high melt index low density polyethylene and the modified elastomer is 3.5:2.5:1.2.

[0010] Preferably, among the antioxidants, the mass ratio of the hindered phenol antioxidant 1010 to the phosphite antioxidant 168 is 3:2.

[0011] Preferably, the above-mentioned 105°C temperature-resistant B1 grade highly flame-retardant cable material is used in high-voltage cables for new energy vehicles, and the thickness of the insulation layer of the high-voltage wire harness for the new energy vehicle is 0.25mm-0.35mm.

[0012] Compared with the prior art, the advantages of the present invention are: 1. The present invention overcomes the defect of the prior art that the glue is easily broken during high-speed wire release, and effectively improves production capacity.

[0013] 2. The present invention breaks through the contradiction in the prior art that it is difficult to achieve both thin-wall and high flame retardancy.

[0014] 3. The present invention solves the problems of increased brittleness and decreased scratch resistance caused by the high-filled flame retardant system in the prior art, and meets the use requirements in extreme environments.

[0015] 4. The present invention meets the increasingly stringent environmental protection requirements for automotive wires, while improving the safety of material use.

[0016] 5. The present invention avoids the instability problem caused by complex formula or difficult process control in the prior art, and reduces production difficulty and cost. DETAILED DESCRIPTION

[0017] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0018] Embodiment 1: A 105°C temperature-resistant B1 grade highly flame-retardant cable material, comprising material A and material B, the mass percentage of material A and material B being 7:3, wherein material A: 35% low melt index high-density polyethylene, 25% high melt index low-density polyethylene, 10% modified elastomer, 4% micron-grade aluminum hydroxide, 3% magnesium hydroxide, 3% expanded graphite, 5% halogen-free phosphorus-nitrogen flame retardant, 1.5% antioxidant, 0.3% lubricant, 3.2% compatibilizer, 5% silane coupling agent, and 5% initiator; material B: 70% high melt index high-density polyethylene, 20% red phosphorus microencapsulated particles, 3% catalyst, 5% antioxidant, and 2% lubricant.

[0019] A method for preparing a 105°C temperature-resistant B1-grade highly flame-retardant cable material, comprising the following steps: S1. Add the first base resin and the first flame retardant into a high-speed mixer, set the speed to 1000 rpm, and mix for 3-5 minutes; S2, add the first compatibilizer and antioxidant, continue mixing for 2 minutes, add the silane coupling agent dropwise during the mixing process, and keep the mixer running at 300-500 rpm for 3-5 minutes to ensure that the silane is evenly coated on the filler surface; S3, putting the dry mixed materials into a twin-screw extruder for melt mixing; S4, adding initiator during extrusion to ensure full dispersion, the extruded material is cooled through a water tank, and cut into granules by a pelletizer to obtain material A; S5, adding the second base resin and the second flame retardant into a high-speed mixer, setting the speed to 1000 rpm, and mixing for 3-5 minutes; S6. Add antioxidant and lubricant, continue mixing for 2 minutes, gradually add catalyst premix to the dry mixed material, keep the mixer running at 300-500 rpm for 2-3 minutes to ensure that the catalyst is evenly dispersed; S7, putting the dry-mixed materials into a twin-screw extruder for mixing, cooling the extruded materials through a water tank, and cutting them into granules with a pelletizer to obtain material B; S8, after material A and material B are evenly mixed, the cable is extruded, the temperature of the extruder is controlled at 180°C, and the pay-off speed is adjusted to 800m / min; S9. Place the processed cable product at 25°C for 48-72 hours to complete the cross-linking reaction.

[0020] Embodiment 2: The difference from embodiment 1 is that, in material A, low melt index high density polyethylene accounts for 40%, high melt index low density polyethylene accounts for 20%, modified elastomer accounts for 8%, micron-grade aluminum hydroxide accounts for 2%, magnesium hydroxide accounts for 1.5%, expanded graphite accounts for 3%, halogen-free phosphorus and nitrogen flame retardant accounts for 3.5%, antioxidant accounts for 2%, and lubricant accounts for 1.8%.

[0021] Embodiment 3: The difference from embodiment 1 is that the low melt index high density polyethylene in material A accounts for 30%, the modified elastomer accounts for 20%, the micron-grade aluminum hydroxide accounts for 2%, the magnesium hydroxide accounts for 1.5%, the expanded graphite accounts for 3%, the halogen-free phosphorus and nitrogen flame retardant accounts for 3.5%, the antioxidant accounts for 3%, the lubricant accounts for 3%, and the compatibilizer accounts for 4%.

[0022] Embodiment 4: The difference from Embodiment 1 is that the low melt index high density polyethylene in material A accounts for 45%, and the high melt index low density polyethylene accounts for 15%.

[0023] Comparative Example 1: The difference from Implementation 1 is that no initiator is added.

[0024] Comparative Example 2: The difference from Implementation 1 is that the proportion of magnesium hydroxide is increased to make it the main component of the flame retardant.

[0025] The materials of the above-mentioned Examples 1-4 and Comparative Examples 1-2 were prepared according to their respective proportions, and were mixed and extruded by a twin-screw extruder. The temperature was set to 180° C., and the materials were formed, cooled and pelletized to prepare standard cable samples. The samples were tested for performance. The test results are shown in Table 1: Table 1 Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Tensile strength (MPa) 32 30 34 33 26 28 Elongation at break (%) 250 240 270 260 200 210 Hardness (Shore A) 85 87 84 86 82 83 Thermal elongation (%) 15 17 18 16 20 22 Strength after heat aging (MPa) 25 24 27 26 20 21 Oxygen index (%) 32 33 30 31 26 28 UL94 flame retardant grade V-0 V-0 V-1 V-0 V-2 V-2 Scratch resistance (mg / cm²) 0.6 0.55 0.65 0.6 0.8 0.75 Antioxidant activity (h) 1000 950 1050 1020 800 850 Chemical resistance No significant changes No significant changes No significant changes Minor changes Obvious changes Obvious changes Low temperature impact performance No cracks No cracks No cracks No cracks There are cracks There are cracks Examples 1 and 3 show high tensile strength, indicating that the selection of the base resin and the optimization of the ratio of the flame retardant filler are helpful to improve the strength of the material. Comparative Example 1 shows low tensile strength, mainly because no initiator is added, resulting in insufficient crosslinking, which affects the overall mechanical properties of the material; Example 3 has the highest elongation at break, reaching 270%, indicating that the formula has good performance in ductility, while Comparative Example 1 has poor elongation, also due to the lack of initiator resulting in unsatisfactory crosslinking effect; the hardness of each example is not much different, ranging from 84 to 87, showing that the material has good hardness and is suitable for long-term use of cables; The hardness of Comparative Examples 1 and 2 is slightly lower, indicating that there may be problems with flame retardant filler replacement or insufficient crosslinking; Examples 2 and 3 have higher elongation at high temperatures, indicating that they are relatively excellent in thermal expansion and thermal stability. The thermal elongation of Comparative Example 1 is higher, which may be due to the lack of initiator, resulting in uneven crosslinking, affecting the thermal stability; the strength of all examples after thermal aging is higher than that of Comparative Examples 1 and 2, proving that in the case of silane crosslinking, the material maintains strong mechanical properties in a high temperature environment; the strength of Comparative Examples 1 and 2 is significantly reduced, indicating that under high temperature aging, the incompletely crosslinked material exhibits poor thermal stability; The oxygen index of Example 2 and Example 1 is relatively high, indicating that they have strong flame retardancy. The oxygen index is an important indicator for measuring the flame retardancy of a material. The higher the value, the more difficult it is for the material to burn. The oxygen index of Comparative Example 1 is relatively low. Since the DCP initiator is not used, the crosslinking process is incomplete, resulting in poor flame retardancy. Example 1, Example 2 and Example 4 all reach the V-0 level, indicating that these formulas have excellent flame retardancy. The flame retardancy level of Comparative Example 1 and Comparative Example 2 is V-2, indicating that their flame retardancy is poor, especially when certain flame retardant ingredients or initiators are not used, the crosslinking is incomplete, resulting in decreased flame retardancy. Example 3 has the best scratch resistance, indicating that it has good wear resistance and scratch resistance. The wear resistance of Example 1 is poor, which may be because the flame retardant filler magnesium hydroxide becomes the main component, causing the material's scratch resistance to decrease; Example 3 and Example 1 show excellent oxidation resistance and can remain stable for a long time under high temperature environment; the oxidation resistance of Examples 1 and 2 is poor, indicating that their anti-aging ability is weak, especially in the case of insufficient crosslinking; the chemical corrosion resistance of all examples is good and there is no obvious change, while the chemical corrosion resistance of Examples 1 and 2 is poor, indicating that the material may experience structural degradation or corrosion when in contact with certain chemicals. The low-temperature impact performance of all examples is good and there is no obvious change, while the low-temperature impact performance of Examples 1 and 2 is poor, indicating that the material may not be used in extreme environments.

[0026] Under the same test conditions, the cable samples of Examples 1-4 and Comparative Examples 1-2 were subjected to the following performance tests, and the test results are shown in Table 2: Table 2 Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Pay-off speed (m / min) 30 28 32 30 24 25 Insulation layer thickness (mm) 0.40 0.38 0.42 0.41 0.45 0.43 Is there any glue breakage? none none none none have have Heavy metal content (ppm) <100 <100 <100 <100 <500 <500 Smoke density (D) (ppm) 50 55 48 52 80 85 Life Cycle Assessment (LCA) excellent excellent excellent excellent medium medium Example 1 and Example 3 show a higher pay-off speed, indicating that the materials of these formulas have good stability and are not easy to break during high-speed pay-off; the pay-off speeds of Comparative Examples 1 and 2 are relatively low, which may be due to the lack of replacement of initiators or flame-retardant fillers, causing greater friction or adhesion of the materials during high-speed pay-off, affecting the pay-off speed; the thickness of the insulation layer of Examples 2 and 3 is relatively stable, ranging from 0.38 to 0.42 mm, which meets the requirements of the insulation layer of conventional automotive cables. The thickness of the insulation layer of Comparative Example 1 is relatively thick, mainly because the flame-retardant filler added to the material formula affects the fluidity of the material during the molding process, resulting in an excessive thickness of the insulation layer; all examples did not experience glue breaking during the high-speed pay-off process, indicating that they have good cross-linking effects and can withstand higher pay-off speeds. Comparative Examples 1 and 2 experienced glue breaking during the pay-off process, indicating that the cross-linking process is insufficient and the insulation layer of the material is prone to fall off or cracking during high-speed stretching.

[0027] The heavy metal contents of all examples are lower than 100ppm, which meets the environmental protection requirements, indicating that these materials perform well in terms of environmental safety. The heavy metal contents of Comparative Examples 1 and 2 are relatively high, which may be due to the fact that some substitutes used do not meet the environmental protection standards, resulting in high heavy metal contents; Example 3 has the lowest smoke density, indicating that it produces less smoke when burned and meets the low-smoke environmental protection requirements. The smoke densities of Comparative Examples 1 and 2 are relatively high, indicating that they produce more smoke when burned, which does not meet the low-smoke environmental protection requirements; the life cycle assessment performance of Example 1, Example 2, Example 3, and Example 4 is excellent, indicating that these materials have little environmental impact in the production, use and disposal stages. The life cycle assessment of Comparative Examples 1 and 2 is relatively poor, which may be due to the fact that some of their components do not meet the environmental protection requirements, resulting in a large environmental impact in the disposal stage.

[0028] The basic principles, main features and advantages of the present invention are shown and described above; those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention and are not used to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected; the scope of protection claimed by the present invention is determined by the attached claims and their effects.

Claims

1. A 105°C temperature resistant B1 grade highly flame retardant cable material, characterized in that: In terms of mass percentage, the cable material includes: 60%-70% of A material and 30%-40% of B material; In terms of mass percentage, the raw materials of the material A include: 60%-85% of the first base resin, 38%-52% of the first flame retardant, 1%-2% of the silane coupling agent, 0.3%-0.5% of the initiator, 2%-4% of the first compatibilizer, 0.3%-0.7% of the antioxidant, and 0.1%-0.3% of the lubricant; In terms of mass percentage, the raw materials of the B material include: 40%-50% of the second base resin, 0.05%-0.1% of the catalyst, 1%-2% of the second flame retardant, 0.3%-0.7% of the antioxidant, and 0.1%-0.3% of the lubricant; The first base resin is composed of low melt index high density polyethylene, high melt index low density polyethylene and modified elastomer, the second base resin is high melt index high density polyethylene, the feed mass ratio of the low melt index high density polyethylene, the high melt index low density polyethylene and the modified elastomer is 3-4:2-3:1-1.5, the melt index of the low melt index high density polyethylene is 0.8-1.5g / 10min, the melt index of the high melt index low density polyethylene is 8-12g / 10min, and the melt index of the high melt index high density polyethylene is 20-30g / 10min; The first flame retardant is composed of micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite and halogen-free phosphorus and nitrogen flame retardant, the second flame retardant is red phosphorus microencapsulated particles, and the mass ratio of micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite and halogen-free phosphorus and nitrogen flame retardant in the first flame retardant is 2-2.5:1-1.5:0.3-0.5:0.5-0.7; The silane coupling agent is vinyl trimethoxysilane, the initiator is diisopropylbenzene peroxide, the first compatibilizer is maleic anhydride grafted ethylene butyl acrylate copolymer, the antioxidant is hindered phenol antioxidant 1010+phosphite antioxidant 168, in the antioxidant, the feed mass ratio of the hindered phenol antioxidant 1010 to the phosphite antioxidant 168 is 2-4:1-3, the lubricant is zinc stearate, and the catalyst is dibutyl tin dilaurate.

2. According to claim 1, a 105°C temperature-resistant B1-grade highly flame-retardant cable material, characterized in that: In the first flame retardant, the mass ratio of micron-sized aluminum hydroxide, magnesium hydroxide, expanded graphite and halogen-free phosphorus and nitrogen flame retardant is 2:1:0.4:0.

6.

3. According to claim 1, a 105°C temperature-resistant B1-grade highly flame-retardant cable material, characterized in that: In the first base resin, the feed mass ratio of the low melt index high density polyethylene, the high melt index low density polyethylene and the modified elastomer is 3.5:2.5:1.

2.

4. According to claim 1, a 105°C temperature-resistant B1-grade highly flame-retardant cable material, characterized in that: Among the antioxidants, the feed mass ratio of the hindered phenol antioxidant 1010 to the phosphite antioxidant 168 is 3:

2.

5. A method for preparing a 105°C temperature-resistant B1-level highly flame-retardant cable material, which relates to a 105°C temperature-resistant B1-level highly flame-retardant cable material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Add the first base resin and the first flame retardant into a high-speed mixer, set the speed to 1000 rpm, and mix for 3-5 minutes; S2, add the first compatibilizer and antioxidant, continue mixing for 2 minutes, add the silane coupling agent dropwise during the mixing process, and keep the mixer running at 300-500 rpm for 3-5 minutes to ensure that the silane is evenly coated on the filler surface; S3, putting the dry mixed materials into a twin-screw extruder for melt mixing; S4, adding initiator during extrusion to ensure full dispersion, the extruded material is cooled through a water tank, and cut into granules by a pelletizer to obtain material A; S5, adding the second base resin and the second flame retardant into a high-speed mixer, setting the speed to 1000 rpm, and mixing for 3-5 minutes; S6. Add antioxidant and lubricant, continue mixing for 2 minutes, gradually add catalyst premix to the dry mixed material, keep the mixer running at 300-500 rpm for 2-3 minutes to ensure that the catalyst is evenly dispersed; S7, putting the dry-mixed materials into a twin-screw extruder for mixing, cooling the extruded materials through a water tank, and cutting them into granules with a pelletizer to obtain material B; S8, after material A and material B are evenly mixed, the cable is extruded, the temperature of the extruder is controlled at 160-200°C, and the pay-off speed is adjusted to 800m / min; S9. Place the processed cable product at 25°C for 48-72 hours to complete the cross-linking reaction.

6. The method for preparing a 105°C temperature-resistant B1-grade highly flame-retardant cable material according to claim 5, characterized in that: The extruder temperature in S8 is 180°C.

7. An application of a 105°C temperature-resistant B1-grade highly flame-retardant cable material as described in any one of claims 1 to 4 in a high-voltage cable for a new energy vehicle, comprising a high-voltage wire harness for a new energy vehicle, wherein the thickness of the insulation layer of the high-voltage wire harness for the new energy vehicle is 0.25mm-0.35mm.

Citation Information

Patent Citations

  • Silane self-crosslinking halogen-free low-smoke flame-retardant polyolefin automobile raw wire material as well as preparation method and application thereof

    CN112409671A